Deficient Rnf43 potentiates hyperactive Kras‐mediated pancreatic preneoplasia initiation and malignant transformation. Issue 1 (22nd January 2022) - Zhou, Xian; Sun, Zhichao; Zhang, Mengdi; Qu, Xiaoyu; Yang, Shuhui; Wang, Lianmei; Jing, Yanling; Li, Li; Deng, Weiwei; Liu, Fangming; Di, Jin; Chen, Jie; et al.
Abstract: Background: Largely due to incidental detection, asymptomatic pancreatic cystic lesions (PCLs) have become prevalent in recent years. Among them, intraductal papillary mucinous neoplasm (IPMN) infrequently advances to pancreatic ductal adenocarcinoma (PDAC). Conservative surveillance versus surgical intervention is a difficult clinical decision for both caregivers and PCL patients. Because RNF43 loss‐of‐function mutations and KRAS gain‐of‐function mutations concur in a subset of IPMN and PDAC, their biological significance and therapeutic potential should be elucidated. Methods: Pancreatic Rnf43 knockout and Kras activated mice ( Rnf43 −/− ; Kras G12D ) were generated to evaluate their clinical significance in pancreatic pre‐neoplastic initiation and malignant transformation. Results: Loss of Rnf43 potentiated the occurrence and severity of IPMN and PDAC in oncogenic Kras mice. The Wnt/β‐catenin signaling pathway was activated in pancreatic Kras G12D and Rnf43 knockout mice and the PORCN inhibitor LGK974 blocked pancreatic IPMN initiation and progression to PDAC accordingly. Conclusions: Rnf43 is a tumor suppressor in the prevention of pancreatic malignant transformation. This genetically reconstituted autochthonous pancreatic Rnf43 −/− ; Kras G12D preclinical cancer model recapitulates the pathological process from pancreatic cyst to cancer in humans and can be treated with inhibitors of Wnt/β‐catenin signaling. Since the presence of RNF43 and KRAS mutations in IPMNs predicts future development of advanced neoplasia from PCLs, patients with these genetic anomalies warrant surveillance, surgery, and/or targeted therapeutics such as Wnt/β‐catenin inhibitors. Abstract : Pancreatic Rnf43 knockout and Kras activated mice ( Rnf43 −/− ; Kras G12D ) develop from pancreatic cysts to pancreatic ductal adenocarcinoma which can be blunted by suppression of Wnt/β‐catenin signaling pathway.